Transcriptional Alterations of Mouse Trigeminal Ganglion Neurons Following Orofacial Inflammation Revealed by Single-Cell Analysis - Liu, Qing; Mai, Lijia; Yang, Shengyan; Jia, Shilin; Chu, Yanhao; He, Hongwen; Fan, Wenguo; Huang, Fang (Frontiers in Cellular Neuroscience, 2022)
Orofacial inflammation leads to transcriptional alterations in trigeminal ganglion (TG) neurons. However, diverse alterations and regulatory mechanisms following orofacial inflammatory pain in different types of TG neurons remain unclear. Here, orofacial inflammation was induced by injection of complete Freund’s adjuvant (CFA) in mice. After 7 days, we performed single-cell RNA-sequencing on TG cells of mice from control and treatment groups. We identified primary sensory neurons, Schwann cells, satellite glial cells, oligodendrocyte-like cells, immune cells, fibroblasts, and endothelial cells in TG tissue. After principal component analysis and hierarchical clustering, we identified six TG neuronal subpopulations: peptidergic nociceptors (PEP1 and PEP2), non-peptidergic nociceptors (NP1 and NP2), C-fiber low-threshold mechanoreceptors (cLTMR) and myelinated neurons (Nefh-positive neurons, NF) based on annotated marker gene expression. We also performed differential gene expression analysis among TG neuronal subtypes, identifying several differential genes involved in the inflammatory response, neuronal excitability, neuroprotection, and metabolic processes. Notably, we identified several potential novel targets associated with pain modulation, including Arl6ip1, Gsk3b, Scn7a, and Zbtb20 in PEP1, Rgs7bp in PEP2, and Bhlha9 in cLTMR. The established protein–protein interaction network identified some hub genes, implying their critical involvement in regulating orofacial inflammatory pain. Our study revealed the heterogeneity of TG neurons and their diverse neuronal transcriptomic responses to orofacial inflammation, providing a basis for the development of therapeutic strategies for orofacial inflammatory pain.